Glutamatergic Ventral Pallidal Neurons Modulate Activity of the Habenula–Tegmental Circuitry and Constrain Reward Seeking - Tooley, Jessica (Biol Psychiatry, 2018)
BACKGROUND: The ability to appropriately integrate and respond to rewarding and aversive stimuli is essential for survival. The ventral pallidum (VP) plays a critical role in processing both rewarding and aversive stimuli. However, the VP is a heterogeneous structure, and how VP subpopulations integrate into larger reward networks to ultimately modulate these behaviors is not known. We identify a noncanonical population of glutamatergic VP neurons that play a unique role in responding to aversive stimuli and constraining inappropriate reward seeking. METHODS: Using neurochemical, genetic, and electrophysiology approaches, we characterized glutamatergic VP neurons (n = 4–8 mice/group). We performed patch clamp and in vivo electrophysiology recordings in the lateral habenula, rostromedial tegmental nucleus, and ventral tegmental area to determine the effect of glutamatergic VP neuron activation in these target regions (n = 6–10 mice/group). Finally, we selectively optogenetically stimulated glutamatergic VP neurons in a real-time place preference task and ablated these neurons using a virally expressed caspase to determine their necessity for reward seeking. RESULTS: Glutamatergic VP neurons exhibit little overlap with cholinergic or gamma-aminobutyric acidergic markers, the canonical VP subtypes, and exhibit distinct membrane properties. Glutamatergic VP neurons innervate and increase firing activity of the lateral habenula, rostromedial tegmental nucleus, and gamma-aminobutyric acidergic ventral tegmental area neurons. While nonselective optogenetic stimulation of the VP induced a robust place preference, selective activation of glutamatergic VP neurons induced a place avoidance. Viral ablation of glutamatergic VP neurons increased reward responding and abolished taste aversion to sucrose. CONCLUSIONS: Glutamatergic VP neurons constitute a noncanonical subpopulation of VP neurons. These glutamatergic VP neurons increase activity of the lateral habenula, rostromedial tegmental nucleus, and gamma-aminobutyric acidergic ventral tegmental area neurons and adaptively constrain reward seeking.